Social-economic and environment impacts for a fish reverse supply chain: A mixed integer linear optimization approach - Iwan Vanany; Ivan Darma Wangsa; Niken Anggraini Savitri; Rizki Revianto Putera; Muhammad Cholili; Berto Mulia Wibawa; Lukman Atmaja; Ming-Lang Tseng (Cleaner Logistics and Supply Chain)
This study contributes to the fish reverse supply chain due to a lack of social, economic and environmental impacts. This study aims to develop a mathematical model for the fish reverse supply chain with a multi-echelon, multiple periods, and products. The model optimizes total profit, job opportunities, and carbon emissions simultaneously. The proposed model provides social-economic insight for governments and industries to understand the increasing job opportunities if fish gelatine and powder industries can process fish waste. A sensitivity analysis shows that the supply of raw fish, selling prices, and purchasing costs are sensitive to total profit, carbon emissions, and job opportunities. The results show that the total profit for five months is USD 1,437,837, and the most significant contribution to the total cost is the costs of purchasing, emission costs, and production costs, which are 43.83%, 24.02%, and 18.15%, respectively. These results can assist managers in making optimal decisions regarding raw fish supply, halal fish gelatine, and fish powder production, impacting strategic, tactical, and operational policies.